Greek Tragedy - Miller - Chmelíková, Linda (Univerzita Pardubice, 2013)
The aim of this work is to focus on the tragic elements in Arthur Miller's A View from the Bridge and determine whether the play meets the criteria and can be classified as Greek tragedy. To reach the conclusions various theories and examples of tragedies are used. Other important aspects such as historical and cultural background and social commentaries within the play are analyzed. In addition, where the play fits in the context of American drama at the time the play was written will be discussed.
Řecká tragédie - Miller
Keywords: Miller, Arthrur; Pohled z mostu; řecká tragédie; divadlo; Aristotléles; View from the Bridge; Greek tragedy; drama; Aristotle